MINAT PETANI PADI SAWAH TERHADAP PENGGUNAAN KREDIT USAHA RAKYAT (KUR) DI KECAMATAN TELUK DALAM KABUPATEN NIAS - Ameilia Zuliyanti Siregar; Makruf Wicaksono; Sonialai Angelina Dachi (Jurnal Agrisep, 2022)
Rice Farmers' Interest in the Use of People's Business Credit (KUR) in Teluk Dalam District, South Nias Regency, North Sumatra Province. The purpose is to determine the level of interest and the factors that influence it. This study was conducted from April 2022 to July 2022. The data collection method is observation, questionnaires and interviews. The data analysis method used Likert scale and multiple linear regression. The results show that level of interest of farmers to the use of People's Business Credit is moderate with an interest level of 48.2%. The results of multiple linear regression on the factors that influence farmers' interest obtain the following equation Y= -6.646 + 0.357 X1 + 0.093 X2 + 0.733 X3 - 0.486 X4. Further tests using t-count showed that the characteristics of farmers, the socialization of the KUR program and the characteristics of the KUR program had a significant influence with the t-count value greater than the t-table. Meanwhile, the involvement of agricultural instructors has no effect with t-count smaller than t-table.